Histological Analysis of the Structural Composition of Ankle Ligaments. (February 2015) - Rein, Susanne; Hagert, Elisabet; Schneiders, Wolfgang; Fieguth, Armin; Zwipp, Hans
Background: Various ankle ligaments have different structural composition. The aim of this study was to analyze the morphological structure of ankle ligaments to further understand their function in ankle stability. Methods: One hundred forty ligaments from 10 fresh-frozen cadaver ankle joints were dissected: the calcaneofibular, anterior, and posterior talofibular ligaments; the inferior extensor retinaculum, the talocalcaneal oblique ligament, the canalis tarsi ligament; the deltoid ligament; and the anterior tibiofibular ligament. Hematoxylin-eosin and Elastica van Gieson stains were used for determination of tissue morphology. Results: Three different morphological compositions were identified: dense, mixed, and interlaced compositions. Densely packed ligaments, characterized by parallel bundles of collagen, were primarily seen in the lateral region, the canalis tarsi, and the anterior tibiofibular ligaments. Ligaments with mixed tight and loose parallel bundles of collagenous connective tissue were mainly found in the inferior extensor retinaculum and talocalcaneal oblique ligament. Densely packed and fiber-rich interlacing collagen was primarily seen in the areas of ligament insertion into bone of the deltoid ligament. Conclusions: Ligaments of the lateral region, the canalis tarsi, and the anterior tibiofibular ligaments have tightly packed, parallel collagen bundles and thus can resist high tensile forces. The mixed tight and loose, parallel oriented collagenous connective tissue of the inferior extensor retinaculum and the talocalcaneal oblique ligament support the dynamic positioning of the foot on the ground. The interlacing collagen bundles seen at the insertion of the deltoid ligament suggest that these insertion areas are susceptible to tension in a multitude of directions. Clinical Relevance: The morphology and mechanical properties of ankle ligaments may provide an understanding of their response to the loads to which they are subjected.